Well-Being in Graduate Medical Education: A Call for Action. (July 2017) - Ripp, Jonathan A.; Privitera, Michael R.; West, Colin P.; Leiter, Richard; Logio, Lia; Shapiro, Jo; Bazari, Hasan
Abstract : Job burnout is highly prevalent in graduate medical trainees. Numerous demands and stressors drive the development of burnout in this population, leading to significant and potentially tragic consequences, not only for trainees but also for the patients and communities they serve. The literature on interventions to reduce resident burnout is limited but suggests that both individual- and system-level approaches are effective. Work hours limitations and mindfulness training are each likely to have modest benefit. Despite concerns that physician trainee wellness programs might be costly, attention to physician wellness may lead to important benefits such as greater patient satisfaction, long-term physician satisfaction, and increased physician productivity. A collaborative of medical educators, academic leaders, and researchers recently formed with the goal of improving trainee well-being and mitigating burnout. Its first task is outlining this framework of initial recommendations in a call to action. These recommendations are made at the national, hospital, program, and nonwork levels and are meant to inform stakeholders who have taken up the charge to address trainee well-being. Regulatory bodies and health care systems need to be accountable for the well-being of trainees under their supervision and drive an enforceable mandate to programs under their charge. Programs and individuals should develop and engage in a "menu" of wellness options to reach a variety of learners and standardize the effort to ameliorate burnout. The impact of these multilevel changes will promote a culture where trainees can learn in settings that will sustain them over the course of their careers.